2020
DOI: 10.17221/151/2019-swr
|View full text |Cite
|
Sign up to set email alerts
|

Potassium fractions in soil and simple K balance in long-term fertilising experiments

Abstract: Experiments were used to determine the potassium release from the non-exchangeable K (Kne) forms that are involved in plant nutrition and which replenish the pool of available K. Long-term stationary field experiments with different fertilisation systems (organic: farmyard manure, sewage sludge, straw; mineral: NPK, N) were carried out to study the potassium balance and the K content changes in the topsoil (0–30 cm) and subsoil (30–60 cm). The trials were located at three sites with different soil-climatic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Previous works have suggested that the recycling of organic K is the major pathway for plant K. This explains the increased AK with the increasing rates of manure replacement [44,45]. Similar observations happened in the study by Balík et al [46]. In addition, increases in organic fertilization stimulate/improve the microbial conversion of organic K into inorganic K.…”
Section: Total and Available P And K In Soilsupporting
confidence: 78%
“…Previous works have suggested that the recycling of organic K is the major pathway for plant K. This explains the increased AK with the increasing rates of manure replacement [44,45]. Similar observations happened in the study by Balík et al [46]. In addition, increases in organic fertilization stimulate/improve the microbial conversion of organic K into inorganic K.…”
Section: Total and Available P And K In Soilsupporting
confidence: 78%
“…It plays crucial roles in many physiological and developmental processes of plants, such as osmotic adjustment, phloem loading and sugar transport to heterotrophic organs, water relations, stomatal regulation, enzyme activation and resistance to biotic and abiotic stresses (Urrego et al, 2014;Wang et al, 2013). However, with the increases in nitrogen (N) and phosphorus (P) fertilizer applications and the release of higher-yielding crop varieties (Dong et al, 2010;Hu et al, 2016), a negative K + balance in soil (around − 60 kg ha − 1 every year) occurred and is becoming worse (Balik et al, 2020;Steiner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The productivity of grain crops under the conditions of each specific field is a dynamic indicator and depends primarily on the presence of moisture in the soil horizon, effective soil fertility, humus content and thickness of its horizon, relief and illumination of the land [14][15][16]. The increase in the stress resistance of cultivated plants to an unfavorable environmental factor and harmful organisms is very important for the promotion of geoinformation technologies [17,18]. In this regard the purpose of our research in 2019-2021. was the improvement of precision farming technology in the production of grain crops in the forest-steppe of Western Siberia.…”
Section: Introductionmentioning
confidence: 99%